Diversity of the soil microbial community and its functional aspects in man-influenced environments - Chroňáková, Alica (Jihočeská univerzita, 2009)
Diversity of the soil microbial community and its functional aspects were investigated in man-influenced environments, such as colliery spoil heaps in post mining sites and upland pasture used for outdoor cattle husbandry. The study was based on the cultivation of bacteria and streptomycetes as well as culture-independent approaches. Cultivated bacteria and streptomycetes were characterized by phenotypic and genotypic means. The culture-independent approaches were based on an analysis of environmental DNA in terms of both qualitative and quantitative parameters.
Diversity of the soil microbial community and its functional aspects in man-influenced environments
Keywords: primary succession; heterotrophic bacteria; diversity; streptomycetes; ancient bacteria; growth strategy; microbial markers; Miocene sediment; colliery spoil heaps; community DNA; denitrifying bacteria; methanogenes; upland pasture; cattle outdoor husbandry; spatial distribution; abundance; microbial activity; nitrous oxide; methane; primary succession; heterotrophic bacteria; diversity; streptomycetes; ancient bacteria; growth strategy; microbial markers; Miocene sediment; colliery spoil heaps; community DNA; denitrifying bacteria; methanogenes; upland pasture; cattle outdoor husbandry; spatial distribution; abundance; microbial activity; nitrous oxide; methane